Aldol condensation reaction catalyst, preparation method and application thereof
By preparing silicone alkali metal catalysts with amorphous structure and suitable mesoporous properties, the problems of poor activity of existing catalysts and difficulty in industrial application are solved, and efficient aldol condensation reaction is achieved, and product yield and catalyst selectivity are improved.
Patent Information
- Application Number
- CN202311107925.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing catalysts have poor activity in the aldol condensation reaction, the target product yield is low, and the preparation process is complicated, making it difficult to achieve industrial application.
A catalyst containing silicon, oxygen and alkali metal elements has the characteristics of amorphous structure, large mesoporous volume and moderate specific surface area. It is prepared by stirring or grinding and mixing, combined with steam treatment and calcining steps to form an efficient active center.
The activity of the catalyst and the yield of the target product are significantly improved, the selectivity of the catalyst is ensured, and the preparation process is simplified, suitable for large-scale industrial applications, and environmentally friendly.
Smart Images

Figure CN119565586A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic chemical reactions, and more specifically to an aldol condensation reaction catalyst, a preparation method and an aldol condensation reaction thereof. Background Art
[0002] Methyl acrylate is an important organic intermediate, which is widely used in rubber, leather, medicine and coating industries. At present, there are several main methods for producing methyl acrylate, propylene oxidation, acrylonitrile hydrolysis and propane oxidation. Industrial production is mainly based on propylene oxidation, which has technical and economic advantages but low efficiency. The acrylonitrile hydrolysis method has a small output and sulfuric acid cannot be recycled. Propane oxidation is a commonly used method, which is cheap but has a low product yield.
[0003] The preparation of methyl acrylate by the condensation reaction of coal-based methyl acetate (or acetic acid) and formaldehyde is a very important and highly productive process synthesis route. It not only has low production costs, but also effectively controls the discharge of polluted waste liquid. It is a synthesis method with great application prospects.
[0004] Chemical Industry Progress, 2021, 40(4): 2005-2015 reported the research progress of acetic acid (ester)-formaldehyde condensation to acrylic acid (ester). The catalysts currently used in this route mainly include VPO catalysts, alkali metal / alkaline earth metal catalysts and ionic liquid catalysts. Among them, VPO catalysts have high catalytic efficiency, but many side reactions and are easily deactivated. Compared with VPO, alkali metal catalysts have no oxidative by-products and higher selectivity, but their catalytic efficiency is slightly lower. Ionic liquid catalysts have mild reaction conditions and high selectivity, but product separation is difficult and the catalyst is difficult to reuse. In comparison, the preparation process of alkali metal catalysts is simpler, the adjustable space is large, the product selectivity is high, and it is easier to achieve industrial application.
[0005] CN 108097290A reports a catalyst for preparing acrylic acid / methyl acrylate from raw materials containing carbon monoxide and formaldehyde compounds. The catalyst is mainly obtained by metal modification of commercially available MOR molecular sieves with different silicon-aluminum ratios using at least one selected from copper, silver, iron, cobalt, nickel and gallium through impregnation, ion exchange and in-situ synthesis. The catalyst has a maximum selectivity of 88.2% for acrylic acid and a selectivity of 5.3% for methyl acrylate.
[0006] The catalyst reported in CN 106693941A has Li, Na, K, Rb, Cs, Mg, Ca, Sr and Ba as active components and Al2O3 prepared by coprecipitation as a carrier. When the molar ratio of methyl acetate: formaldehyde: methanol is 1:2:2, the conversion rate of methyl acetate is 34.4% and the selectivity of methyl acrylate is 93.4%.
[0007] CN 104258901A discloses a Cs-loaded pure silicon molecular sieve catalyst, which uses KIT-6 as a carrier and Cs of different contents as an active component. The catalyst is applied to the reaction of preparing methyl acrylate by aldol condensation of methyl acetate and formaldehyde. The molar ratio of methyl acetate, formaldehyde and methanol is 1:2:2. The conversion rate of methyl acetate can reach up to 35%, and the selectivity of methyl acrylate can reach up to 94%.
[0008] Teng He et al. reported in Catalysis Letters, 2019, 149(2):373-389 that cesium-loaded SiO2 was used as a catalyst and different contents of Cs as the active component in the reaction of methyl acetate and formaldehyde aldol condensation to prepare methyl acrylate. The molar ratio of methyl acetate, formaldehyde, and methanol was 1:2:2. At a reaction temperature of 390°C, the conversion rate of methyl acetate was about 35%, and the selectivity of methyl acrylate was 85-90%.
[0009] Among various catalysts for catalyzing the aldol condensation reaction of methyl acetate and formaldehyde to prepare MA, the silica-supported Cs alkali metal catalyst has the best performance, but its activity is not ideal and the yield of the target product is low. Summary of the invention
[0010] The present invention aims to provide an aldol condensation reaction catalyst with high catalytic activity and high yield of target product, and to provide a preparation method thereof and application of the catalyst in the aldol condensation reaction.
[0011] In order to achieve the above object, the present invention provides an aldol condensation reaction catalyst, characterized in that it contains silicon, oxygen and alkali metal elements, has an amorphous structure, and has a micropore volume of less than 0.05 cm 3 / g, mesopore volume greater than 0.55cm 3 / g, with obvious pore distribution in the range of 16-50nm and a specific surface area of 50-300m 2 / g, and the ratio of mesopore volume to total pore volume is (0.9-0.99):1.
[0012] The present invention also provides a method for preparing an aldol condensation reaction catalyst, which is characterized in that silicon dioxide is mixed with an alkali metal hydroxide or salt and an optionally added solvent, the mixture is stirred or ground to be uniformly mixed, and then treated under steam conditions, and finally the treated solid is dried and roasted.
[0013] The present invention further provides a method for aldol condensation, characterized in that, in the presence of the catalyst provided by the present invention or the catalyst obtained by the preparation method provided by the present invention, a carbonyl-containing compound having α-H is subjected to a carbon-carbon bond coupling reaction with another carbonyl-containing compound to generate a carbonyl-containing compound having a β-hydroxyl group or a carbonyl-containing compound having an α,β-unsaturated bond.
[0014] Compared with the prior art, the advantages of the present invention are:
[0015] (1) The catalyst prepared by stirring or grinding with alkali metal as the main active component and silica as the carrier has a very high mesoporous ratio, which can provide a rich mesoporous specific surface area to immobilize active centers and enable the alkali metal to be evenly distributed in the carrier silica, thereby ensuring good selectivity of the catalyst and improving its activity.
[0016] (2) The catalyst preparation method is simple, the steps are short, the raw materials are widely available and the raw materials are cheap, which makes it suitable for large-scale industrial application and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is the XRD spectra of Example 1 and Example 7;
[0018] Figure 2 The pore distribution diagrams of Example 1, Example 7 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0019] The present invention provides an aldol condensation reaction catalyst, which is characterized by containing silicon, oxygen and alkali metal elements, having an amorphous structure, and a micropore volume of less than 0.05 cm 3 / g, mesopore volume greater than 0.55cm 3 / g, with obvious pore distribution in the range of 16-50nm and a specific surface area of 50-300m 2 / g, and the ratio of mesopore volume to total pore volume is (0.9-0.99):1.
[0020] The catalyst provided by the present invention is characterized as an amorphous structure by XRD, that is, there is no obvious sharp characteristic peak in the spectrum; XRF characterization shows that it contains silicon, oxygen and alkali metal elements. The catalyst is characterized by N2 adsorption and desorption method, and the BET specific surface area is 50-300m 2 / g, preferably 70-250m 2 / g, more preferably 90-200m 2 / g, more preferably 100-160m 2 / g. The aldol condensation reaction catalyst provided by the present invention has an extremely high mesopore ratio, and can provide abundant mesopore specific surface area to immobilize active centers. The ratio of the mesopore volume to the total pore volume of the catalyst is (0.9-0.99):1, preferably (0.95-0.99):1, and further preferably (0.98-0.99):1.
[0021] In the catalyst provided by the present invention, the alkali metal element is selected from one or more of lithium, sodium, potassium, rubidium, and cesium, preferably one or more of potassium, rubidium, and cesium, more preferably one or more of rubidium and cesium, and further preferably cesium. Preferably, the alkali metal element is uniformly dispersed in the silicon dioxide.
[0022] The catalyst provided by the present invention obtains the molar ratio of each element in the catalyst by X-ray fluorescence spectrometer analysis method (XRF). The molar ratio of the alkali metal element to the silicon element is (0.001-0.1):1, preferably (0.005-0.08):1, further preferably (0.01-0.06):1, and more preferably (0.02-0.05):1.
[0023] The catalyst provided by the present invention has a pore volume of less than 0.05 cm 3 / g, preferably less than 0.03cm 3 / g, more preferably less than 0.02cm 3 / g; mesopore volume is greater than 0.55cm 3 / g, preferably greater than 0.60cm 3 / g, more preferably greater than 0.70cm 3 / g, and a large mesopore volume is beneficial to the efficient distribution of active centers; the catalyst provided by the present invention has an obvious pore distribution in the range of 16-50nm.
[0024] In the catalyst provided by the present invention, the ratio of the specific surface area of the matrix to the specific surface area of the micropores is preferably (1-7):1, further preferably (2-6):1, and more preferably (3-5):1. The matrix is the non-micropore part, and the specific surface area of the matrix = BET specific surface area - specific surface area of the micropores
[0025] In the Si NMR spectrum, Q 4 (-113ppm) represents Si(OSi)4 species, Q 3 (-103ppm) represents Si(OSi)3(OH) species. Characterized by NMR silicon spectrum, it can be found that the catalyst provided by the present invention has a low Q 3 The signal intensity of silicon species indicates that there are fewer defect sites and the active centers are more evenly dispersed, which is more conducive to the catalytic reaction Q 4 With Q 3The ratio of the signal peak height is greater than 100:1, preferably greater than 150:1, further preferably greater than 200:1, more preferably greater than 250:1, and most preferably 300:1 until there is no Q 3 Signal peak.
[0026] The present invention also provides a method for preparing the above-mentioned aldol condensation reaction catalyst, characterized in that silicon dioxide is mixed with an alkali metal hydroxide or salt and an optionally added solvent, the mixture is stirred or ground to be uniformly mixed, and then treated under steam conditions, and finally the treated solid is dried and calcined to obtain the catalyst.
[0027] In the preparation method, the silicon dioxide is derived from white carbon black or silicon dioxide produced by hydrolysis and precipitation of organic silicon ester. The white carbon black preferably has a SiO2 weight content greater than 99%, more preferably greater than 99.9%; the specific surface area of the white carbon black is preferably 50-1000m 2 / g, more preferably 100-800m 2 / g, more preferably 150-500m 2 / g. Hydrophilic silica is preferred. Hydrophilic silica is more conducive to processing during preparation and loading of active centers than other types of silica, such as oleophilic silica.
[0028] The organosilicon ester is preferably tetraalkoxysilane. The tetraalkoxysilane has a structure of R1, R2, R3, R4 (SiO4), wherein R1, R2, R3, R4 are independently C1-C 12 alkyl, alkenyl, alkynyl, aryl substituted groups, and each R group is connected to an oxygen atom of silicon. Preferably, R1, R2, R3, and R4 are independently C2-C4 alkyl, alkenyl, alkynyl, and aryl substituted groups, and further preferably, R1, R2, R3, and R4 are C2-C4 alkyl, alkenyl, alkynyl, and aryl substituted groups, more preferably, R1, R2, R3, and R4 are C2-C4 alkyl substituted groups, and most preferably, R1, R2, R3, and R4 are ethyl and propyl groups. Specifically, the tetraalkoxy silicon can be one or more of tetraethoxy silicon and tetrapropoxy silicon.
[0029] The hydrolysis and precipitation of the organosilicon ester can be carried out under acidic conditions such as pH 6, 5, 4, 3, 2, 1, or under alkaline conditions such as pH 8, 9, 10, 11, 12, 13, 14. The acidic conditions can be provided by inorganic acids and / or organic acids, which can be one or more of hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, acetic acid, and propionic acid. The alkaline conditions can be provided by inorganic bases and / or organic bases, which can be one or more of ammonium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium phosphate, methylamine, ethylamine, propylamine, butylamine, cyclohexylamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and tetrabutylphosphine hydroxide.
[0030] The hydrolysis can be carried out in water or in a solution containing water, for example, in a methanol-water solution. The hydrolysis process can generally be carried out at room temperature and pressure, and the hydrolysis can be accelerated by appropriately increasing the temperature, for example, the hydrolysis can be carried out at a temperature greater than 30° C. The hydrolysis can generally be completed within 0.1-24 hours, and the hydrolysis time can also be adjusted as needed.
[0031] Usually, solid precipitates are produced after hydrolysis, which can be separated by conventional methods such as filtration and centrifugation to obtain precipitates. At this time, the precipitate can be used directly for subsequent operations, or can be dried for subsequent operations, or can be dried and calcined for subsequent operations. Preferably, subsequent operations are performed after drying. The drying is preferably carried out at a temperature range of 60-150°C, more preferably 80-150°C, and more preferably 100-130°C, and the drying time is preferably 0.1-24h, more preferably 0.5-12h, and more preferably 1-6h. The calcination is preferably treated at 350-750°C for 0.5-12h, and the calcination atmosphere is preferably an oxygen-containing atmosphere, and more preferably an air atmosphere.
[0032] In the preparation method, the alkali metal is selected from one or more of lithium, sodium, potassium, rubidium, and cesium, preferably one or more of potassium, rubidium, and cesium, more preferably one or more of rubidium and cesium, and further preferably cesium. The alkali metal element of the present invention is uniformly dispersed in the catalyst.
[0033] In the preparation method, the alkali metal hydroxide or salt includes alkali metal hydroxide, hydrochloride, hypochlorite, chlorite, metachlorate, perchlorate, nitrate, sulfate, hydrogen sulfate, sulfite, bisulfite, phosphate, hydrogen phosphate, dihydrogen phosphate, high phosphate, metaphosphate, phosphite, hypophosphite, carboxylate, pyrophosphate, ammonium salt, C1-C 20One or more of the carboxylates of cesium; preferably nitrates, carbonates, hydroxides of alkali metals; more preferably one or more of cesium hydroxide, cesium nitrate, cesium carbonate, cesium bicarbonate, and cesium acetate.
[0034] In the preparation method, the molar ratio of silicon dioxide (calculated as SiO2) to alkali metal is preferably 1:(0.001-0.1), a further preferred ratio is 1:(0.005-0.08), a more preferred ratio is 1:(0.01-0.06), and the most preferred ratio is 1:(0.02-0.05).
[0035] In the preparation method, the solvent is optional. The solvent can be an inorganic solvent or an organic solvent. The inorganic solvent is distilled water or deionized water; the organic solvent includes an organic solvent selected from C1-C 10 Alcohol, C3-C 10 Ketone, C2-C 10 Esters, C6-C 10 The solvent may be a chlorinated solvent such as dichloromethane. The solvent is an aliphatic alcohol, typically a C1-C6 alkanol, such as methanol, ethanol, propanol, isopropanol, butanol, pentanol and hexanol, preferably methanol, ethanol or propanol. The amount of solvent added depends on the carrier. In the preparation method, the preferred solvent is at least one of water, methanol, ethanol and propanol. The molar ratio of silicon dioxide (calculated as SiO2) to solvent is preferably 1: (0-10), further preferably 1: (0.5-7), and more preferably 1: (1-4).
[0036] In the preparation method, the mixing is uniform, and one or more of stirring method, impregnation method, ion exchange method, spraying method, solid phase ion exchange method and grinding method can be used, and it can be repeatedly used for many times, among which stirring method or grinding method is preferred. Compared with other methods, the grinding method can make the alkali metal and silicon dioxide contact better, and a grinding chemical reaction occurs, which is more conducive to the formation of the catalytic active center described in the present invention, so the grinding method is more preferably used. The grinding is preferably carried out at 20-150°C, more preferably 30-100°C, and more preferably 40-70°C for 5-120min, preferably 10-80min, and more preferably 15-60min; the grinding can be carried out at a pressure (gauge pressure) of -0.1-5MPa. Both negative pressure and positive pressure conditions are conducive to the distribution of alkali metal elements, but it also brings the problem of high energy consumption.
[0037] In the preparation method, the treatment under steam conditions is carried out under water vapor at 100-200°C, preferably 120-180°C, more preferably 130-160°C, and a gauge pressure of 0-1MPa, preferably 0.1-0.8MPa, more preferably 0.3-0.6MPa for 0.1-24h, preferably 1-12h, and further preferably 2-8h. The steam can be superheated steam or saturated steam. The pressure can be adjusted by supplementing gas, such as nitrogen, argon, air, etc. After treatment under steam conditions, the mesoporous volume can be increased, the distribution of alkali metal elements can be promoted, and efficient active centers can be formed.
[0038] In the preparation method, the treated solid is dried and calcined, wherein the drying condition is 60-150°C, preferably in the temperature range of 80-130°C. The drying time is 0.5-24h, preferably 0.5-12h, and more preferably 1-6h. In the calcination conditions, the calcination temperature is determined according to the decomposition temperature of the modifier alkali element precursor, but is preferably <550°C to prevent the alkali element precursor from decomposing. The calcination temperature is further preferably 400-550°C. To prevent a significant change in the carrier structure or specific surface area, the calcination time is 0.5-12h, preferably 3-8h; the calcination atmosphere is preferably an oxygen-containing atmosphere, and more preferably an air atmosphere.
[0039] The present invention further provides a method for aldol condensation, characterized in that, in the presence of the catalyst provided by the present invention or the catalyst obtained by the preparation method provided by the present invention, a carbonyl-containing compound having α-H is subjected to a carbon-carbon bond coupling reaction with another carbonyl-containing compound to generate a carbonyl-containing compound having a β-hydroxyl group or a carbonyl-containing compound having an α,β-unsaturated bond.
[0040] The α and β positions refer to the functional groups of hydrocarbon molecules, such as carbonyl, hydroxyl, carboxyl, etc., and the carbon atoms of the first ortho and second ortho positions. The carbonyl-containing compound includes the first carbonyl compound and the second carbonyl compound, and the carbon number of the carbonyl compound is preferably C1-C 20 . The carbonyl compound may include the following structure:
[0041] C1-C 12Alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl; preferably C1-C6 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, and particularly preferably C1-C4 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isohexyl, sec-butyl and tert-butyl.
[0042] C3-C 12 Cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl and cyclododecyl; preferably cyclopentyl, cyclohexyl and cycloheptyl.
[0043] Examples of substituted cycloalkyl groups are: 2-methylcyclopentyl, 3-methylcyclopentyl, 2-methylcyclohexyl, 3-methylcyclohexyl, 4-methylcyclohexyl, 2-methoxycyclopentyl, 2-chlorocyclopentyl, 2-methylthiocyclohexyl and other derivatives.
[0044] C7-C 13 Arylalkyl, preferably C7-C 12 Phenylalkyl, such as benzyl, 1-phenylethyl, 2-phenylethyl, 1-phenylpropyl, 2-phenylpropyl, 3-phenylpropyl, 1-phenylbutyl, 2-phenylbutyl, 3-phenylbutyl and 4-phenylbutyl, particularly preferably benzyl;
[0045] C6-C 14 Aryl, for example phenyl, 1-naphthyl, 2-naphthyl, 1-anthryl, 2-anthryl, 9-anthryl, 1-phenanthrenyl, 2-phenanthrenyl, 3-phenanthrenyl, 4-phenanthrenyl, 9-phenanthrenyl, preferably phenyl, which is unsubstituted or substituted with one or more of the following groups:
[0046] C1-C 12 Alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl; preferably C1-C6 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, and particularly preferably C1-C4 alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isohexyl, sec-butyl and tert-butyl.
[0047] Halogen, such as fluorine, chlorine, bromine, iodine, preferably chlorine.
[0048] C1-C 12 Alkoxy, preferably C1-C6 alkoxy, such as methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, isopentylpropoxy, n-hexyloxy and isohexyloxy, particularly preferably methoxy, ethoxy, n-propoxy, n-butoxy.
[0049] Preferably, the first carbonyl compound contains α-H, and the second carbonyl compound contains α-H or does not contain α-H.
[0050] Further preferably, the carbonyl compound not containing α-H is preferably formaldehyde, benzaldehyde, furfural, 5-hydroxyfurfural, 5-methylfurfural or their derivatives, and formaldehyde is further preferred; the carbonyl compound containing α-H is preferably acetaldehyde, propionaldehyde, acetone, butyraldehyde, butanone, valeraldehyde, pentanone, hexanal, hexanone, cyclohexanone, cyclopentanone, acetic acid, propionic acid, malonic acid, butyric acid, succinic acid, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, cyclohexyl acetate, methyl propionate, ethyl propionate, butyl propionate, dimethyl malonate, methyl butyrate, dimethyl succinate, ethyl butyrate or at least one of their derivatives.
[0051] In the aldol condensation method, the molar ratio of the first carbonyl compound to the second carbonyl compound is 1:(0.1-10), further preferably 1:(0.2-6), more preferably 1:(0.4-4), more preferably 1:(0.8-3), and most preferably 1:(1-2).
[0052] In the aldol condensation method, the carbonyl compound mixed stream further comprises one or more diluents, the diluents comprising at least one of alcohols, ethers, alkanes, halogenated alkanes, and toluene, preferably methanol, cycloalkane, ether, and toluene. The molar ratio of the diluent to the carbonyl compound is (30-0.5):1, preferably (20-0.7):1, further preferably (10-0.8):1, more preferably (5-0.9):1, and most preferably (3-1):1.
[0053] In the aldol condensation method, the aldol condensation reaction is preferably carried out in an atmosphere containing at least one gas selected from the group consisting of N2, He, Ar, CH4, C2H6, H2, CO, and CO2, and more preferably in an atmosphere containing N2.
[0054] In the aldol condensation method, the aldol condensation reaction temperature is 300-500° C., preferably 320-400° C., more preferably 340-380° C. Before the reaction, the temperature of the mixed solution is preferably raised to between 300-400° C., more preferably between 340-400° C. The reaction pressure is 0-5 MPa, preferably 0-1.5 MPa, more preferably 0-1.0 MPa in gauge pressure.
[0055] In the aldol condensation method, the hourly space velocity of the reaction liquid is 0.05-5h, based on the total mass of the carbonyl compound and the diluent. -1 , preferably 0.08-3h -1 , more preferably 0.1-2.5h -1 .
[0056] According to the process of the present invention, the formaldehyde source is an anhydrous formaldehyde source, preferably methylal, trioxymethylene and paraformaldehyde. The inventors have found that the catalyst according to the present invention is able to surprisingly improve the activity and selectivity for the condensation of a methylene source such as formaldehyde with a carboxylic acid or a hydrocarbyl ester such as methyl acetate to form an olefinically unsaturated carboxylic acid.
[0057] In the aldol condensation method, an optional specific implementation method is that formaldehyde and methyl acetate undergo an aldol condensation reaction, and the conditions include: a methyl acetate: formaldehyde molar ratio of 5:2 to 1:1, a methanol: methyl acetate molar ratio of 1:1 to 2:1, a reaction temperature of 340 to 380°C, a reaction pressure (gauge pressure) of 0 to 1.0 MPa, a nitrogen flow rate of 30 to 100 mL / min, and a reaction liquid hourly space velocity of 0.1 to 2.5 h -1 The space velocity should be understood as the mass space velocity, which means the ratio of the mass flow rate of the total mass of the reactant substrate and the diluent (in units of (mass / time)) to the mass of the catalyst. Therefore, the unit of the space velocity is h -1 .
[0058] In the aldol condensation method, another optional specific embodiment is that formaldehyde and methyl propionate undergo an aldol condensation reaction, and the conditions include: the molar ratio of methyl propionate: formaldehyde is 1:2 to 1:0.2, the molar ratio of methanol: methyl propionate is 1:1 to 5:1, the reaction temperature is 320 to 400°C, the reaction pressure (gauge pressure) is 0 to 1 MPa, the nitrogen flow rate is 30 to 100 mL / min, and the reaction liquid hourly space velocity is 0.1 to 2 h -1 .
[0059] The method of aldol condensation is preferably carried out in a fixed bed reactor, a fluidized bed reactor or a kettle reactor. It will be appreciated by those skilled in the art that, depending on the different reactors used, the catalyst of the present invention can be a catalyst powder modified by alkaline metal elements, or a shaped catalyst modified by alkaline metal elements, and the weight proportion of the aldol condensation reaction catalyst in the catalyst can be 5%-100%. The separation of the product and the catalyst can be achieved in a variety of ways. For example, when the catalyst modified by the original powdered alkaline metal element is used as the catalyst, the separation of the product and the recycling of the catalyst can be achieved by sedimentation, filtration, centrifugation, evaporation, membrane separation and the like. Alternatively, the catalyst can also be loaded into a fixed bed reactor after being shaped, and the catalyst can be recovered after the reaction is completed. The separation and recovery methods of various catalysts are often involved in the existing literature, which will not be described here.
[0060] The present invention is described in detail below by way of examples.
[0061] N2 adsorption and desorption characterization and analysis: Autosorb 6B static nitrogen adsorption instrument, produced by Quantachrome.
[0062] Test conditions: After the sample is loaded, the temperature is raised to 300°C and the vacuum is evacuated to 1.33×10 -2 Pa, constant temperature and pressure for 4 hours to purify the sample. Then characterize it at liquid nitrogen -196℃. The specific surface area is calculated by BET formula, and the pore volume of the sample is calculated by p / p 0 The adsorption capacity was calculated under the condition of ≤0.98, and the pore size distribution was calculated by the BJH formula.
[0063] X-ray fluorescence spectrometer (XRF): ZSX100E X-ray fluorescence spectrometer, produced by Rigaku Co., Ltd., Japan.
[0064] Test conditions: The sample was tested after being pressed into a sheet, tungsten-palladium, the excitation voltage was 40 kV, and the excitation current was 250 mA.
[0065] X-ray powder diffraction (XRD): Empyrean X-ray diffractometer, produced by Philips.
[0066] Test conditions: CuKα ray, λ=0.15406nm, 2θ scanning range: 5°-35°.
[0067] The catalytic performance test adopts a fixed bed reactor at normal pressure to catalyze the aldol condensation of methyl acetate and formaldehyde to synthesize methyl acrylate with the prepared catalyst. The molar ratio of methyl acetate to formaldehyde is 1:1, methanol is used as solvent, the molar ratio of methyl acetate to methanol is 1:2, and the feed space velocity of the raw material mixture is 1h -1The amount of catalyst was 5 g; the carrier gas (N2) flow rate was maintained at 50 mL / min during the reaction, and the reaction temperature was 360° C. The product was condensed and then subjected to chromatographic analysis.
[0068] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels and are all pure reagents.
[0069] The analysis methods in the examples and comparative examples of the present application are as follows:
[0070] The composition of the reaction product was analyzed by gas chromatography, and the analysis results were quantified by external standard method. The chromatographic analysis conditions were: Agilent 6890 chromatograph, HP5 capillary column, injection volume 0.5 μL, injection port temperature 280°C. The column temperature was maintained at 100°C for 2 min, then increased to 200°C at a rate of 15°C / min and maintained for 3 min. FID detector, detector temperature 300°C.
[0071] The calculations of conversion, selectivity and yield in the examples are as follows:
[0072]
[0073] Y 丙烯酸甲酯 =C 醋酸甲酯 ×S 丙烯酸甲酯
[0074] Comparative Example 1
[0075] Tetraethyl silicate (TEOS) and a hydrochloric acid solution with a pH of 3 were mixed in a molar ratio of 1:30, hydrolyzed at 40°C for 6 hours, and the obtained solid was separated by filtration. The solid was dried at 120°C for 6 hours, and then calcined at 500°C for 3 hours to obtain a carrier amorphous silica.
[0076] Silicon dioxide, cesium carbonate and water were mixed, wherein the molar ratio of silicon to cesium was 1:0.03, and the molar ratio of silicon to solvent was 1:40. The mixture was stirred at normal pressure and 40°C for 30 minutes, and then the solvent was evaporated to obtain a solid. The solid was dried at 120°C for 6 hours, and then calcined at 400°C for 6 hours to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0077] Comparative Example 2
[0078] SBA-15 molecular sieve, cesium carbonate and water were mixed, wherein the molar ratio of silicon to cesium was 1:0.03, and the molar ratio of silicon to solvent was 1:40. The mixture was stirred at normal pressure and 40°C for 30 minutes, and then the solvent was evaporated to obtain a solid. The solid was dried at 120°C for 6 hours, and then calcined at 400°C for 6 hours to obtain Cs / SBA-15. The catalyst was characterized and evaluated, and the results are shown in Table 1. The pore distribution diagram of the sample of Comparative Example 2 is shown in Figure 2 , there is an obvious pore distribution in the range of 6-8nm. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0079] Example 1
[0080] Tetraethyl silicate (TEOS) and a hydrochloric acid solution with a pH of 3 were mixed in a molar ratio of 1:30, hydrolyzed at 40°C for 6 hours, and the obtained solid was separated by filtration. The solid was dried at 120°C for 6 hours, and then calcined at 500°C for 3 hours to obtain a carrier amorphous silica.
[0081] Silica, cesium carbonate and water were mixed, wherein the molar ratio of silicon to cesium was 1:0.03, and the molar ratio of silicon to solvent was 1:2. The mixture was stirred at normal pressure and 40°C for 30 minutes, and then the solvent was evaporated to obtain a solid. The solid was treated with water vapor at 120°C and normal pressure for 3 hours, further dried at 120°C for 6 hours, and then calcined at 400°C for 6 hours to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The XRD spectrum of the sample in Example 1 is shown in Figure 1 The XRD spectrum shows a large broad peak at 24°, which is a characteristic peak of amorphous silica. After alkali metal modification, no impurity peaks appear, indicating that the alkali metal is evenly distributed in silica. See the pore distribution diagram Figure 2 ,from Figure 2 It can be seen that the modified silica has an obvious pore distribution in the range of 16-32 nm. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0082] Example 2
[0083] Tetraethyl silicate (TEOS) and hydrochloric acid solution with a pH of 3 were mixed in a molar ratio of 1:30, hydrolyzed at 60°C for 6 hours, and the obtained solid was separated by filtration. The solid was dried at 100°C for 6 hours, and then calcined at 550°C for 6 hours to obtain a carrier amorphous silica.
[0084] Silicon dioxide, cesium nitrate and water were mixed, wherein the molar ratio of silicon to cesium was 1:0.04, and the molar ratio of silicon to solvent was 1:4. The mixture was stirred at 1MPa pressure (gauge pressure) and 60°C for 60 minutes, and then the solvent was evaporated to obtain a solid. The solid was treated with water vapor at 180°C and normal pressure for 2 hours, further dried at 100°C for 3 hours, and then calcined at 500°C for 3 hours to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0085] Example 3
[0086] Tetraethyl silicate (TEOS) and a hydrochloric acid solution with a pH of 3 were mixed in a molar ratio of 1:30, hydrolyzed at 40° C. for 6 h, and the obtained solid was separated by filtration. The solid was dried at 120° C. for 6 h to obtain a carrier amorphous silica.
[0087] Silicon dioxide, cesium nitrate and water were mixed, wherein the molar ratio of silicon to cesium was 1:0.03, and the molar ratio of silicon to solvent was 1:2. The mixture was ground at 0.5MPa pressure (gauge pressure) and 40°C for 30min to obtain a solid. The solid was treated with water vapor at 120°C and 0.2MPa pressure (gauge pressure) for 3h, further dried at 120°C for 6h, and then calcined at 400°C for 3h to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0088] Example 4
[0089] Tetraethyl silicate (TEOS) and an aqueous ammonia solution with a pH of 11 were mixed in a molar ratio of 1:30, hydrolyzed at 40° C. for 12 hours, and the obtained solid was separated by filtration. The solid was dried at 120° C. for 3 hours to obtain a carrier amorphous silica.
[0090] Silica, cesium carbonate and water were mixed, wherein the molar ratio of silicon to cesium was 1:0.02, and the molar ratio of silicon to solvent was 1:4. The mixture was ground at 0.3MPa pressure (gauge pressure) and 50°C for 15min to obtain a solid. The solid was treated with water vapor at 180°C and 0.8MPa pressure (gauge pressure) for 5h, further dried at 130°C for 2h, and then calcined at 450°C for 8h to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0091] Example 5
[0092] Tetraethyl silicate (TEOS) and a hydrochloric acid solution with a pH of 3 were mixed in a molar ratio of 1:30, hydrolyzed at 60° C. for 6 h, and the obtained solid was separated by filtration. The solid was dried at 100° C. for 6 h to obtain a carrier amorphous silica.
[0093] Silicon dioxide, cesium nitrate and ethanol were mixed, wherein the molar ratio of silicon to cesium was 1:0.04, and the molar ratio of silicon to solvent was 1:2. The mixture was ground at 0.5MPa pressure (gauge pressure) and 60°C for 30min to obtain a solid. The solid was treated with water vapor at 170°C and 0.8MPa pressure (gauge pressure) for 8h, further dried at 120°C for 3h, and then calcined at 400°C for 5h to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0094] Example 6
[0095] Tetraethyl silicate (TEOS) and a hydrochloric acid solution with a pH of 3 were mixed in a molar ratio of 1:30, hydrolyzed at 40° C. for 6 h, and the obtained solid was separated by filtration. The solid was dried at 120° C. for 3 h to obtain a carrier amorphous silica.
[0096] Silica, cesium hydroxide and water were mixed, wherein the molar ratio of silicon to cesium was 1:0.03, and the molar ratio of silicon to solvent was 1:2. The mixture was ground at 0.7MPa pressure (gauge pressure) and 70°C for 15min to obtain a solid. The solid was treated with water vapor at 120°C and 0.25MPa pressure (gauge pressure) for 4h, further dried at 110°C for 5h, and then calcined at 500°C for 8h to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0097] Example 7
[0098] The specific surface area is 200m 2 / g of hydrophilic white carbon black is mixed with cesium nitrate and water, wherein the molar ratio of silicon to cesium is 1:0.03, and the molar ratio of silicon to solvent is 1:2. The mixture is ground at -0.3MPa pressure (gauge pressure) and 40°C for 15 minutes to obtain a solid. The solid is treated with water vapor at 130°C and 0.3MPa pressure (gauge pressure) for 3 hours, further dried at 120°C for 6 hours, and then calcined at 400°C for 6 hours to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The XRD spectrum of the sample in Example 7 is shown in Figure 1 The XRD spectrum shows a large broad peak at 24°, which is a characteristic peak of amorphous silica. After alkali metal modification, no impurity peaks appear, indicating that the alkali metal is evenly distributed in silica. See the pore distribution diagram Figure 2 ,from Figure 2 It can be seen that the modified silica has obvious pore distribution in the range of 32-50nm. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0099] Example 8
[0100] The specific surface area is 200m 2 / g of hydrophilic white carbon black was mixed with cesium hydroxide and water, wherein the molar ratio of silicon to cesium was 1:0.05, and the molar ratio of silicon to solvent was 1:1. The mixture was ground at -0.5MPa pressure (gauge pressure) and 70°C for 30min to obtain a solid. The solid was treated with water vapor at 160°C and 0.6MPa pressure (gauge pressure) for 5h, further dried at 130°C for 5h, and then calcined at 400°C for 3h to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0101] Example 9
[0102] The specific surface area is 400m 2 / g of hydrophilic white carbon black was mixed with cesium carbonate and water, wherein the molar ratio of silicon to cesium was 1:0.03, and the molar ratio of silicon to solvent was 1:4. The mixture was ground at -0.4MPa pressure (gauge pressure) and 50°C for 60min to obtain a solid. The solid was treated with water vapor at 150°C and 0.47MPa pressure (gauge pressure) for 8h, further dried at 110°C for 3h, and then calcined at 450°C for 5h to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1.
[0103] The evaluation results of the aldol condensation reaction are shown in Table 2.
[0104] Example 10
[0105] The specific surface area is 400m 2 / g of hydrophilic white carbon black was mixed with cesium nitrate and ethanol, wherein the molar ratio of silicon to cesium was 1:0.04, and the molar ratio of silicon to solvent was 1:3. The mixture was ground at -0.3MPa pressure (gauge pressure) and 60°C for 30min to obtain a solid. The solid was treated with water vapor at 140°C and 0.36MPa pressure (gauge pressure) for 4h, further dried at 120°C for 5h, and then calcined at 500°C for 6h to obtain Cs / SiO2. The catalyst was characterized and evaluated, and the results are shown in Table 1. The evaluation results of the aldol condensation reaction are shown in Table 2.
[0106] Table 1
[0107]
[0108] Table 2
[0109] Example Methyl acetate conversion rate / % Methyl acrylate selectivity / % Methyl acrylate yield / % Comparative Example 1 32 72 23 Comparative Example 2 37 74 27 Example 1 78 88 69 Example 2 79 88 70 Example 3 79 90 71 Example 4 80 89 71 Example 5 81 89 72 Example 6 81 90 73 Example 7 84 92 77 Example 8 85 92 78 Example 9 83 91 76 Example 10 83 91 76
[0110] From the comparative data of Examples 1-10 and Comparative Examples 1-2 in Table 2, it can be seen that the aldol condensation reaction catalyst of the present invention has unique physicochemical characteristics and can significantly improve the raw material conversion rate and product yield. The by-products of the present invention are mainly isobutylaldehyde, methacrolein, methyl methacrylate, etc., while the by-products of the comparative examples contain acetone, acetic acid, etc.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An aldol condensation reaction catalyst, characterized in that Contains silicon, oxygen and alkali metal elements, has an amorphous structure, and the micropore volume is less than 0.05cm 3 / g, the mesopore volume is greater than 0.55cm 3 / g, with obvious pore distribution in the range of 16-50nm and a specific surface area of 50-300m 2 / g, the ratio of mesopore volume to total pore volume is (0.9-0.99):1, the catalyst is characterized by NMR silicon spectrum, the ratio of -113ppm signal peak height to -103ppm signal peak height Q 4 / Q 3 >100, where Q 4 represents Si(OSi)4 species, Q 3 Represents Si(OSi)3(OH) species.
2. The catalyst according to claim 1, characterized in that The catalyst is obtained by mixing silicon dioxide with alkali metal hydroxide or alkali metal salt and an optionally added solvent, stirring or grinding the mixture to make it uniform, then treating it under steam conditions, and finally drying and roasting the treated solid.
3. The catalyst according to claim 1, characterized in that The pore volume of micropores is less than 0.03 cm 3 / g, preferably less than 0.02cm 3 / g; mesopore volume is greater than 0.60cm 3 / g, preferably greater than 0.70cm 3 / g.
4. The catalyst according to claim 1, characterized in that The Q 4 / Q 3 >150, preferably >200, more preferably >250, most preferably >300.
5. The catalyst according to claim 1, characterized in that The catalyst was characterized by NMR silica spectrum, which showed no -103 ppm signal peak.
6. The catalyst according to claim 1, characterized in that The alkali metal element is selected from one or more of lithium, sodium, potassium, rubidium and cesium, preferably one or more of potassium, rubidium and cesium, more preferably one or more of rubidium and cesium, and most preferably cesium.
7. The catalyst according to claim 1, characterized in that The molar ratio of the alkali metal element to the silicon element is (0.001-0.1):1, preferably (0.005-0.08):1, further preferably (0.01-0.06):1, and more preferably (0.02-0.05):
1.
8. The catalyst according to claim 1, characterized in that The ratio of the matrix specific surface area to the micropore specific surface area is (1-7):1, preferably (2-6):1, and more preferably (3-5):
1.
9. A method for preparing an aldol condensation reaction catalyst, characterized in that: Silicon dioxide is mixed with an alkali metal hydroxide or salt and an optionally added solvent, stirred or ground to mix evenly, then treated under steam conditions, and finally the treated solid is dried and calcined. The treatment under steam conditions is water vapor at 100-200°C, preferably 120-180°C, more preferably 130-160°C, and a gauge pressure of 0-1MPa, preferably 0.1-0.8MPa, more preferably 0.3-0.6MPa for 0.1-24h, preferably 1-12h, and further preferably 2-8h.
10. The preparation method according to claim 9, characterized in that: The silicon dioxide is selected from white carbon black or silicon dioxide produced by hydrolysis and precipitation of organic silicon ester.
11. The preparation method according to claim 9, characterized in that: The white carbon black has a SiO2 weight content greater than 99% and a specific surface area of 50-1000m 2 / g.
12. The preparation method according to claim 9, characterized in that: The white carbon black has a SiO2 weight content greater than 99.9% and a specific surface area of preferably 50-1000m 2 / g, preferably 100-800m 2 / g, more preferably 150-500m 2 / g.
13. The preparation method according to claim 9, characterized in that: The white carbon black is hydrophilic white carbon black.
14. The preparation method according to claim 9, characterized in that: The organic silicon ester is tetraalkoxy silicon, and the tetraalkoxy silicon has the structure of R1, R2, R3, R4 (SiO4), wherein R1, R2, R3, R4 are independently C1-C 12 The alkyl, alkenyl, alkynyl, and aryl substituent groups are each connected to an oxygen atom of silicon.
15. The preparation method according to claim 14, characterized in that: The tetraalkoxy silicon is tetraethoxy silicon and / or tetrapropoxy silicon.
16. The preparation method according to claim 9, characterized in that: The alkali metal salt is selected from the group consisting of alkali metal hydrochlorides, hypochlorites, chlorites, metachlorites, perchlorates, nitrates, sulfates, bisulfates, sulfites, bisulfites, phosphates, hydrogen phosphates, dihydrogen phosphates, high phosphates, metaphosphates, phosphites, hypophosphites, carboxylates, pyrophosphates, C1-C 20 One or more of the carboxylates.
17. The preparation method according to claim 9, characterized in that: The alkali metal salt is cesium nitrate, cesium carbonate, cesium bicarbonate, and cesium acetate, and the alkali metal hydroxide is cesium hydroxide.
18. The preparation method according to claim 9, characterized in that: The molar ratio of the silicon dioxide to the solvent is 1:(0-10), preferably 1:(0.5-7), and more preferably 1:(1-4), wherein the silicon dioxide is calculated as SiO2.
19. The preparation method according to claim 9 or 18, characterized in that: The solvent is at least one of water, methanol, ethanol and propanol.
20. The preparation method according to claim 9, characterized in that: The stirring or grinding is carried out for 5-120 minutes at a gauge pressure of -0.1 MPa to -0.5 MPa and a temperature of 20-150°C.
21. An aldol condensation reaction catalyst obtained according to the preparation method of any one of claims 9 to 20.
22. An aldol condensation reaction method, characterized in that: In the presence of the catalyst of any one of claims 1 to 8 or the catalyst of claim 21, a first carbonyl-containing compound having α-H and a second carbonyl-containing compound undergo a carbon-carbon bond coupling reaction to generate a carbonyl-containing compound having a β-hydroxyl group or a carbonyl-containing compound having an α,β-unsaturated bond.
23. The reaction method according to claim 22, characterized in that The first carbonyl compound contains α-H, and the second carbonyl compound contains α-H or does not contain α-H.
24. The reaction method according to claim 22, characterized in that: The first carbonyl compound has a structure as shown in the following formula (1), and the second carbonyl compound has a cyclic ketone, a structure as shown in the following formula (1), formula (2) or formula (3): Wherein, each of R1 to R2 is independently selected from one or more of hydrogen, a halogen group, an alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms, a substituted or unsubstituted aryl group having 6 to 14 carbon atoms, and an alkoxy group having 1 to 12 carbon atoms; The R4 to R6 are each independently selected from one or more of a halogen group, an alkyl group having 1 to 12 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms, a substituted or unsubstituted aryl group having 6 to 14 carbon atoms, and an alkoxy group having 1 to 12 carbon atoms; The R3, R7-R8 are each independently selected from one or more of hydrogen, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, and a substituted or unsubstituted furyl group having 4 to 20 carbon atoms; The cyclic ketone is selected from substituted or unsubstituted cyclic ketones having 4 to 8 carbon atoms; Preferably, the halogen group is selected from one or more of fluorine, chlorine, bromine and iodine, preferably chlorine; The alkyl group having 1 to 12 carbon atoms is one or more selected from the group consisting of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, sec-pentyl, neopentyl, 1,2-dimethylpropyl, isopentyl, n-hexyl, isohexyl, sec-hexyl, n-heptyl, isoheptyl, n-octyl, n-nonyl, n-decyl and n-dodecyl, and is preferably methyl; The unsubstituted cycloalkyl group is selected from one or more of cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cycloundecyl and cyclododecyl; the substituent on the substituted cycloalkyl group is selected from one or more of alkyl groups having 1 to 9 carbon atoms, preferably one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; more preferably, the substituted or unsubstituted cycloalkyl group having 3 to 12 carbon atoms is selected from one or more of cyclopentyl, cyclohexyl and cycloheptyl; The unsubstituted aryl group is selected from one or more of phenyl, naphthyl, anthracenyl and phenanthrenyl, wherein the substituent on the substituted aryl group is selected from an alkyl group having 1 to 8 carbon atoms, preferably one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl; more preferably, the substituted or unsubstituted aryl group having 6 to 14 carbon atoms is selected from one or more of phenyl, benzyl, propylphenyl and butylphenyl, further preferably phenyl; The alkoxy group having 1 to 12 carbon atoms is selected from one or more of methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, sec-butoxy, tert-butoxy, n-pentoxy, isopentylpropoxy, n-hexyloxy and isohexyloxy, preferably one or more of methoxy, ethoxy, n-propoxy and n-butoxy; The substituent on the substituted furanyl group is selected from one or more of methyl, ethyl and hydroxymethyl; The unsubstituted cyclic ketone is selected from one or more of cyclopentanone, cyclohexanone and octacyclic ketone, wherein the substituent on the substituted cyclic ketone is selected from one or more of methyl, ethyl, n-propyl and isopropyl.
25. The reaction method according to claim 22, characterized in that: The first carbonyl compound is selected from one or more of acetaldehyde, propionaldehyde, acetone, butanone, hexanone, methyl acetate, ethyl acetate, methyl propionate and methyl butyrate, preferably methyl propionate; the second carbonyl compound is selected from one or more of cyclohexanone, cyclopentanone, methyl acetate, ethyl acetate, methyl propionate, methyl butyrate, 2,2-dimethylpropionate, 2,2-dimethylpropionaldehyde, formaldehyde, benzaldehyde, furfural, 5-hydroxyfurfural and 5-methylfurfural, preferably formaldehyde.
26. The reaction method according to claim 22, characterized in that The molar ratio of the second carbonyl compound to the first carbonyl compound is 1:(0.1-10), preferably 1:(0.2-6), further preferably 1:(0.4-4), more preferably 1:(0.8-3), and most preferably 1:(1-2).
27. The reaction method according to claim 22, characterized in that: The carbonyl compound mixed stream also contains one or more diluents, the diluent includes at least one of alcohols, ethers, alkanes, halogenated alkanes, and toluene, preferably methanol, cycloalkanes, ether, and toluene; the molar ratio of the diluent to the carbonyl compound is (30-0.5):1, preferably (20-0.7):1, further preferably (10-0.8):1, more preferably (5-0.9):1, and most preferably (3-1):
1.
28. The reaction method according to claim 22, characterized in that It is the aldol condensation reaction between formaldehyde and methyl acetate. The method comprises: a molar ratio of methyl acetate to formaldehyde of 5:2 to 1:1, a molar ratio of methanol to methyl acetate of 1:1 to 2:1, a reaction temperature of 340 to 380°C, a reaction gauge pressure of 0 to 1.0 MPa, a nitrogen flow rate of 30 to 100 mL / min, and a reaction liquid hourly space velocity of 0.1 to 2.5 h -1 .
29. The reaction method according to claim 22, characterized in that The aldol condensation reaction of formaldehyde and methyl propionate is carried out under the following conditions: the molar ratio of methyl propionate to formaldehyde is 1:2 to 1:0.2, the molar ratio of methanol to methyl propionate is 1:1 to 5:1, the reaction temperature is 320 to 400°C, the reaction gauge pressure is 0 to 1 MPa, the nitrogen flow rate is 30 to 100 mL / min, and the reaction liquid hourly space velocity is 0.1 to 2 h -1 .
Citation Information
Patent Citations
Aldol condensation catalyst, and preparation method and application thereof
CN102188967A
A process for production of a silica-supported alkali metal catalyst
CN104703696A
Aldol condensation catalyst, preparation method and method for preparing methyl methacrylate by using aldol condensation catalyst
CN112675830A
Composite catalytic material containing skeleton heteroatom molecular sieve as well as preparation method and application of composite catalytic material
CN116174017A
Process for synthesizing mesoporous SiO2 melecular sieve with cubic structure
CN1342607A